PERAN ORANG TUA DALAM MENANAMKAN PENDIDIKAN KARAKTER ANAK MENURUT PANDANGAN ISLAM: Studi Kasus Tegal Panjang Desa Wibawa Mulya Kabupaten Bekasi - Taufik Hidayat; Masykur H Mansyur; Jaenal Abidin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
Having bad character at an early age cannot be tolerated just because he is still small, the character possessed by early childhood will greatly affect his growth. Child character education is very important to instill in children from an early age. Parents are the first education for children, therefore parents play an important role in the growth of children's character. The purpose of this study was to analyze the role of parents in instilling children's character education according to Islamic views in Tegal Panjang, Wibawa Mulya Village, Bekasi Regency. This type of research that researchers do uses descriptive qualitative methods. The sampling technique used purposive sampling technique. Data analysis used there are three activity paths, namely data reduction, data display, drawing conclusions. are: first, the exemplary method; Parents first exemplify good character first, such as speaking softly, speaking politely and inviting children to worship together. Second, Habit Method; such as, accustoming children to dispose of trash in its place, washing hands before eating, accustoming children to praying on time and reciting the Koran in non-formal educational institutions. Third, the method of advice and stories; Parents choose stories that contain advice to shape children's character through stories contained in the Qur'an. Fourth, the method of discipline; like children accustomed to sleep on time and pray on time. Fifth, the method of participation; forms of parental participation in the form of physical and non-physical